Parvalbumin Neurons in Zona Incerta Regulate Itch in Mice - Li, Jiaqi; Bai, Yang; Liang, Yi; Zhang, Yiwen; Zhao, Qiuying; Ge, Junye; Li, Dangchao; Zhu, Yuanyuan; Cai, Guohong; Tao, Huiren; Wu, Shengxi; Huang, Jing (Frontiers in Molecular Neuroscience, 2022)
Pain and itch are intricately entangled at both circuitry and behavioral levels. Emerging evidence indicates that parvalbumin (PV)-expressing neurons in zona incerta (ZI) are critical for promoting nocifensive behaviors. However, the role of these neurons in itch modulation remains elusive. Herein, by combining FOS immunostaining, fiber photometry, and chemogenetic manipulation, we reveal that ZI PV neurons act as an endogenous negative diencephalic modulator for itch processing. Morphological data showed that both histamine and chloroquine stimuli induced FOS expression in ZI PV neurons. The activation of these neurons was further supported by the increased calcium signal upon scratching behavior evoked by acute itch. Behavioral data further indicated that chemogenetic activation of these neurons reduced scratching behaviors related to histaminergic and non-histaminergic acute itch. Similar neural activity and modulatory role of ZI PV neurons were seen in mice with chronic itch induced by atopic dermatitis. Together, our study provides direct evidence for the differential roles of ZI PV neurons in regulating itch and pain, and identifies a potential target for the remedy of chronic itch.